Optic Nerve Aplasia. Issue 1 (March 2022) - Saffren, Brooke D.; Yassin, Shaden H.; Geddie, Brooke E.; de Faber, Jan Tjeerd H. N.; Blieden, Lauren S.; Bhate, Manjushree; Gamio, Susana; Rutar, Tina; Levin, Alex V.
Abstract : Objective: Optic nerve aplasia (ONA) is a rare ocular anomaly. We report ophthalmologic, systemic, and genetic findings in ONA. Methods: Patients were identified through an International Pediatric Ophthalmology listserv and from the practice of the senior author. Participating Listserv physicians completed a data collection sheet. Children of all ages were included. Neuroimaging findings were also recorded. Results: Nine cases of ONA are reported. Patients' ages ranged from 10 days to 2 years (median 9 months). Seven cases were bilateral. All patients had absence of the optic nerve and retinal vessels in the affected eye or eyes. Ophthalmologic findings included glaucoma, microcornea, persistent pupillary membrane, iris coloboma, aniridia, retinal dysplasia, retinal atrophy, chorioretinal coloboma, and persistent fetal vasculature. Systemic findings included facial dysmorphism, cardiac, genitourinary, skeletal, and developmental defects. A BCOR mutation was found in one patient. One patient had rudimentary optic nerves and chiasm on imaging. Conclusion: ONA is a unilateral or bilateral condition that may be associated with anomalies of the anterior or posterior segment with or without systemic findings. Rudimentary optic nerve on neuroimaging in one case suggests that ONA is on the continuum of optic nerve hypoplasia.